O programa de desenvolvimento educacional do Paraná (PDE/PR): permanência e avanço em relação às políticas de formação continuada dos anos 1990 - Duarte, Luzia Franco (2014)
The liberal education reforms of the 1990 play an important role in the formulation of teacher education policies in the State of Paraná. With the advent of new functions for school education and the rescue of the emphasis on improving the quality of education, in the XXI century the elaboration and implementation of an educational policy of continuing education in the Requião government (2003-2010) is sustained by the interlocution between Education and Higher Education. Therefore, this study takes as its object the analysis of the Educational Development Program of the State of Paraná (PDE / PR) as a public policy aimed at the continuing education of teachers of the public school system. The research focuses on signaling the continuities and advances that underpinned this proposal of continuing education of teachers of Basic Education in Paraná (2007-2012) in relation to the policies of teacher training of the 1990s. It is used as a theoretical- Analytical method of historical-dialectical materialism for the analysis and understanding of the primary and secondary sources pertinent to the research object. In order to meet the central objective, it is firstly to trace the course of teacher training policies that preceded and succeeded the PDE / PR; In the second moment, the analytical characterization of the pedagogical and political proposal of the documents that guided the said Program is carried out; Finally, it is sought to indicate the continuities and advances of the PDE / PR in relation to the policies of continuing education of teachers of the State Education Network in Paraná from the years of 1990. As a final considerations, the interfaces Of the relationship between the University and the School due to the formative interlocution between the Basic Education and the Higher Education, besides reflecting on the characteristics of permanence and progress that the PDE / PR presents with the policies implemented from the years of 1990 in the formation Teacher in the State of Paraná.